(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
In recent years, the incidence of gynecological malignant tumors during pregnancy has increased, mainly due to an increase in the number of pregnant women in old age. The most common gynecological malignant tumors during pregnancy are cervical cancer (71.6%), followed by ovarian malignancies (7.0%). The incidence of cervical cancer in pregnancy itself is not very high, and symptoms can be easily confused with other diseases during pregnancy. During pregnancy, gynecological examination is limited, which means that the likelihood of a misdiagnosis is higher. Treatment for cervical cancer during pregnancy is associated with many factors, such as tumor size, pathological type, gestational age, lymph node involvement, and the patient’s desire to maintain the pregnancy. Due to these factors, it is difficult to determine the optimal treatment. This article looks at the progress in research into the diagnosis and treatment of cervical cancer in pregnancy to balance effective tumor management with protecting fetal health, while avoiding treatment delays and premature birth.